Formation of ultracold ground-state CsYb molecules via Feshbach-optimized photoassociation. (15th September 2020) - Sun, Zhi-Xin; Hai, Yang; Lyu, Bing-Kuan; Wang, Gao-Ren; Cong, Shu-Lin
Abstract: We investigate theoretically the formation of ultracold ground-state CsYb molecules on the lowest vibrational level via the Feshbach-optimized photoassociation process. Three s-wave Feshbach resonances of CsYb are found. The probability density of the scattering state in the short-range internuclear distance is significantly enhanced near the resonance positions. The population transfer efficiency reaches its maximum when the pulse duration equals half a period of the Rabi oscillation. By using the optimized laser parameters including the peak intensity and detuning, the final population of the lowest vibrational level of the ground electronic state reaches order of 10 −1 in the four-laser scheme.